Hubungan antara Konformitas dengan Perilaku Konsumtif Pembelian Fashion secara Online pada Wanita Karir - Dhea Ayu Ardani (Arden Jaya Publisher, 2023)
This study aims to determine whether there is a relationship between conformity with consumptive behavior in online fashion purchases in career women. The study used two scales, namely the conformity scale based on aspects of conformity is proposed by Myers (2010) is Informational Influence and Normative Influence and the consumptive behavior scale based on behavioral aspects proposed by Engel, Blackwell, and Miniard (2005) is Impulsive Buying, Non-rational Buying and Wasteful Buying. The subjects of this study were 95 career women and the sampling technique used is saturation sampling. then analyzing the data using simple linear regression using the SPSS application version 25.0 for Windows. The results of the study prove that there is a significant positif relationship between conformity with consumptive behavior in in online fashion purchases in career women with the coefficient results showing of siginificance 0.000 (<0.05) with result r= 0.544.